Dialog Iman dan Budaya: Mendalami Pengalaman Hidup Beriman Umat Paroki St. Mikhael, Labasa-Muna, Sulawesi Tenggara - Katu, Yulius (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
The writer tries to analyse the encounter between Christian faith and the local culture particularly that of Muna culture of Southeast Sulawesi. Formerly the missionaries seemed to come in with their particular theological framework, while the local people live in their inherited way of life and traditional rites, such as worshipping their ancestors, ritual to sacred places, etc. The missiological challenges would be, how the Christian faith could be accepted fully by the local people and the Christian values could also support the dynamic of the local culture. The answer would be openness of both sides. From the Church’s side, it is actually a challenge in fostering contextual theology, particularly following the anthropological model. Opennes to learn the richness of the local culture is jus a must.